Towards sustainable partnerships in global health: the case of the CRONICAS Centre of Excellence in Chronic Diseases in Peru - Miranda, JJ (2016)
Describes the experience of the CRONICAS Centre of Excellence in Chronic Diseases, based at Universidad Peruana Cayetano Heredia in Lima, Peru, as a case study for fostering meaningful and sustainable partnerships for international collaborative research. In defiant contexts, partnerships require to be nurtured and sustained. Acknowledging that all partnerships are not and should not be the same, we also need to learn from the evolution of such relationships, its key successes, hurdles and failures to contribute to the promotion of a culture of global solidarity where mutual goals, mutual gains, as well as mutual responsibilities are the norm.